Exploring Water Consumption in Dhaka City Using Instrumental Variables Regression Approaches - Muhammad Shahadat Hossain Siddiquee; Raihan Ahamed (Environmental Processes, 2020)
This paper explores water consumption in Dhaka city for better understanding of its usage, and considers the implications of findings from distributive rationale. Using 459 household survey data collected by BRAC Institute of Governance and Development (BIGD), this study estimates income elasticities of water consumption after controlling the effects of other covariates including wealth-proxies, location, household size, water bill and spatial zones using the instrumental variable regression (IVREG) and instrumental variable quantile regression (IVQREG) approaches. The latter has an additive advantage over the former as the IVQREG provides a more accurate picture of the relationship of water consumption with the income throughout the entire water consumption distribution. Using the fixed pay variable as instrument, findings reveal the strong evidence that income is endogenous. The IVQREG results show that income elasticities are heterogeneous and vary significantly across the water quantiles, implying inequality in water consumption. It also provides strong systematic evidence as income elasticity of water consumption decreases with the increase in percentile. Significant spatial inequality in water consumption from IVREG approach disappears as we use IVQREG. This also strongly supports the systematic evidence obtained. Therefore, it is imperative to introduce different tariff structures among different water consumer groups for bringing equity in water consumption and revenue generation. However, Dhaka Water Supply & Sewerage Authority (DWASA) must ensure smart water meter before implementing such tariff structure as we face severe challenges while measuring residential water consumption.